2008
DOI: 10.1016/j.watres.2007.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Sequential anode–cathode configuration improves cathodic oxygen reduction and effluent quality of microbial fuel cells

Abstract: a b s t r a c tThe reduction of oxygen at the cathode and the diffusion of protons from the anode to the cathode are currently perceived as two major bottlenecks of microbial fuel cells (MFCs). To address these issues, we have designed an MFC configuration in which the effluent of an acetate-fed anode was used as a feed for an aerated, biocatalysed cathode. The development of a cathodic biofilm achieved a four-fold increase of the current output compared with the non-catalysed graphite cathode, while the pH va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
88
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(97 citation statements)
references
References 21 publications
8
88
0
1
Order By: Relevance
“…A way to prevent this pH gradient is either to take out the membrane Liu and Logan 2004) or to pump the anolyte to the cathode to guarantee mixing (Freguia et al 2008a). Although it has been shown that both methods prevent the pH gradient to develop, it also causes substrate/product crossover giving unwanted side reactions and products.…”
Section: Implications For Designmentioning
confidence: 99%
“…A way to prevent this pH gradient is either to take out the membrane Liu and Logan 2004) or to pump the anolyte to the cathode to guarantee mixing (Freguia et al 2008a). Although it has been shown that both methods prevent the pH gradient to develop, it also causes substrate/product crossover giving unwanted side reactions and products.…”
Section: Implications For Designmentioning
confidence: 99%
“…The electric voltage is proportional to the electron-driving force from anode to cathode, and the electric current is proportional to the reducing power generated by bacterial cells. The solar cells induce the electron-driving force from anode to cathode, by which the oxidation reaction coupled with bacterial catabolism may be activated in the anode and the reduction reaction of oxygen with protons and electrons may be activated in the cathode [10,39].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of a Mn(IV)-modified anode and a Fe(III)-modified cathode may be ideal for composing an MFC without an electron mediator and oxidant, but not one from which catholyte aeration can be excluded [4,29,32]. In order to compose an MFC without catholyte aeration, the cathode has to function as a catalyst for the electrochemical reaction of protons, electrons, and oxygen [10], and as a redox barrier to conserve the potential difference between the anode and cathode. Graphite felt, to which neutral red (an electron mediator) is immobilized to catalyze electron transfer from bacterial cells to the electrode [30,36], generally has been used as both the anode and cathode, but it is difficult to modify membranes with this material because of its soft and weak structure.…”
mentioning
confidence: 99%
“…The graphite granules have diameters of 1.5-6 mm and a porosity of 45%, leading to a mean nominal surface area of 1,000 cm 2 in each compartment (Freguia et al 2008). …”
Section: Two-compartment Electrochemical Reactor Design and Operationmentioning
confidence: 99%